Effect of Playing Venue on Hormonal Responses and Psychological State of Inter-University Volleyball Players - Yasmeen Tabassum; Muhammad Zafar Iqbal Butt; Nabila Roohi (The Sky)
The home advantage is a powerful wonder that happens in the realm of amateur and professional games where most teams win more than 50% of matches. The present study compared the effects of playing venue on hormonal responses and psychological state of inter-university volleyball players at home and away ground. A total of 96 male players age, 18 to 24 years from eight different public and private universities were selected as the subject in this study. Matches were scheduled in such a manner so that each team would play one match on home ground and one on away ground. The results of this study showed that a 13% reduction in the testosterone level of players was seen on the opponent’s home ground before playing the match, whereas, 18% elevation in cortisol level of players was recorded on the opponent’s home ground before-match. Psychological measures indicated that players’ cognitive and somatic anxiety levels were increased on away ground (10% and 13%, respectively) whereas, their self-confidence level declined  by 17% on an opponent’s home ground before the commencement of the match. The present study supports the notion that there are differences in pre-competition hormonal and psychological states that may play a key role in ‘the home advantage’ which could affect players’ behavior and match outcomes.